Effect of active and passive recovery on blood lactate and performance during simulated competition in high level gymnasts - Jemni, M.; Sands, W. A.; Friemel, F.; Delamarche, P. (Canadian Journal of Applied Physiology, 2003)
The purpose of this study was to investigate the effect of two recovery strategies between men's gymnastics events on blood lactate removal (BL) and performance as rated by expert "blind" judges. Twelve male gymnasts (21.8 +/- 2.4 years) participated. The sessions were composed of routine performances in the six Olympic events, which were separated by 10 min of recovery. All gymnasts performed two recovery protocols between events on separate days: Rest protocol, 10 min rest in a sitting position; Combined protocol, 5 min rest and 5 min self-selected active recovery. Three blood samples were taken at 2, 5, and 10 min following each event. Gymnasts produced moderate values of BL following each of the six events (2.2 to 11.6 mmol.L-1). There was moderate variability in BL values between events that could not be accounted for by the athlete's event performance. Gymnasts showed higher BL concentration (p > .05) and significantly (p < .05) higher scoring performances (as rated by a panel of certified judges) when they used a combined recovery between gymnastics events rather than a passive recovery (delta BL = 40.51% vs. 28.76% of maximal BL, p < .05, and total score = 47.28 +/- 6.82 vs. 38.39 +/- 7.55, p < .05, respectively).